Use of Noninvasive Cerclage in Combination of Micronized Progesterone in Miscarriage Of Multifetal Pregnancy - Iryna Nikitina; Alla Boychuk; Valentina Kondratiuk; Tatyana Babar (Galician Medical Journal, 2017)
We represent the results of the combined method of treatment and prevention of miscarriage in women with a multiple pregnancy and a high risk of the threat of termination the pregnancy because of using the obstetric unloading pessaries, combined with micronized progesterone. The efficiency of this method of treatment is evidenced by the rapid elimination of clinical symptoms of threatened abortion, accelerating the regression of ultrasound markers, reducing the number of complications in of pregnant women and reducing the time of their stay in hospital.